Programa de Observadores a Bordo (POBCh) de la Secretaria de Pesca de la Provincia del Chubut, Argentina . Observer On board Program -Fisheries Secretariat of the Province of Chubut-Argentina (OOBPPCh) ... - Góngora, María Eva (ArOBIS Centro Nacional Patagónico, 2021)
ENGLISH: In Patagonia, Argentina, (from 42º00 SL to 47º00 SL) it is developing an important shrimp fishery, target on "Patagonian Red Shrimp" (Pleoticus muelleri), caught by twin trawler freezer fleet. Since 2001, the survey was optimized and the fishery was surveyed by the Fisheries Secretariat of the Province of Chubut by means OOBPPCh, that collects of the fishery biological information about target specie and by catch, contributing to strengthen knowledge about ecosystem and biodiversity of the fishing areas. Specimens were identified on board by trained observers following a protocol. Also there is wide reference collection of condricthyes and osteicthyes available from the "Working Agreement between the Fisheries Secretariat and Natural Sciences Faculty of the National University of Patagonia San Juan Bosco". Reported observations were recorded in data base of the OOBPPCh. -- ESPAÑOL -- En Patagonia, Argentina (42º00´LS y 47º00´LS) se desarrolla una pesquería cuya especie blanco es el langostino ...